Sustainable absorption panels from agricultural waste / Farrah Zuhaira Ismail … [et al.] - Ismail, Farrah Zuhaira; Rahmat, Mohamad Nidzam; Mohd Yussof, Farrah Norizzah; Mohammad Noor, Mohd Amir Firdaus (Research Innovation Business Unit, 2014)
Noise pollution has become a major concern worldwide. Whilst majority agree at some level that the current traditional sound absorption panels using synthetic materials such as glass, wool, felts or polyester fibres are the solution to the noise problems, others on the other hand voice out concerns on the health and environmental impacts of such materials. Thus, new researches on sustainable sound absorption panels are now trending. There are many researches initiated to study the potential of waste especially agricultural waste as an acoustic panel. Malaysia has plenty of agricultural waste products such as coconut coir fibres, rice husk and palm oil fibres. Therefore this innovation focuses on producing acoustic panels from the combination of two waste; coconut coir fibres and waste paper. Four samples of acoustic panels were fabricated from a mixture of coconut coir powder and shredded waste papers as follow: Sample 1 (25% of coconut coir powder, 75% of shredded waste paper) Sample 2 (50% of coconut coir powder, 50% of shredded waste paper) Sample 3 (75% of coconut coir powder, 25% of shredded waste paper) Sample 4 (100% of coconut coir powder) The measurement of the panels is 0.5m x 0.5m x 0.012m. Gypsum powder was used as the binder. The measurement of sound absorption coefficient of the test sample was conducted in the reverberation chamber. The procedure of the test was carried out in accordance with ISO354:1985 standard. For sample 1 which was a mixture of 25% of coconut coir powder with 75% of shredded waste paper, the absorption coefficient are 0.03, 0.24, 0.26, 0.27, 0.36 and 0.40 at respective frequency of 250Hz, 500 Hz, 1000Hz, 2000Hz, 4000Hz and 8000Hz. it can be seen that more sound were absorbed at higher frequency range. For sample 2, the absorption coefficient are 0.14, 0.16, 0.27, 0.26, 0.30 and 0.26 at respective frequency of 250Hz, 500Hz, 1000Hz, 2000Hz, 4000Hz and 8000Hz. Meanwhile for sample 3 the absorption coefficient are 0.10, 0.16, 0.22, 0.24, 0.26 and 0.24 at respective frequency of 250Hz, 500Hz, 1000Hz, 2000Hz, 4000Hz and 8000Hz. It can be seen that the sound absorption performance had decreased 0.20 at 8000Hz. Sample 4 which contained 100% of coconut coir powder showed that the highest sound coefficient was 0.27 at 1000Hz before it decreased and became stagnant with 0.26 at higher frequency. Since the particle of the coconut coir powder is too small, combining it 100% has resulted in tighter space in the panel thus lowering the ability to absorb the sound. The results indicated that, Sample 1 gave the highest absorption coefficient compared to sample 2, 3 and 4. It can be concluded that the acoustic panel, made from a mixture of 25% coconut coir powder with 75% shredded waste paper provided higher absorption coefficient. This might be caused by the size of the coir powder which is very small, creating less void space in between the panel and thus causing it to absorb less sound.